Atrioventricular Dissociation after Electroconvulsive Therapy - Siegfried William Yu; Srikanth Vallurupalli; Jennifer Arnoldi; Richard Holloway (Cardiology Research and Practice)
Electroconvulsive therapy (ECT) is increasingly used as a treatment for psychiatric disorders. Cardiac effects are the principal cause of medical complications in these patients. We report a case of atrioventricular (AV) dissociation that occurred after ECT that was treated with pacemaker implantation. The mechanisms contributing to the onset of AV dissociation in this patient, and the management and rationale for device therapy, in light of the most recent guidelines, are reviewed.